Phytochemical Screening and Antioxidant Activity of Ethanolic Extract of Cawat Hanoman Stem (Bauhinia aculeata L.) using DPPH Method - Rahmi Muthia; Muhammad Hidayatullah; Rahmi Hidayati (Borneo Journal of Pharmacy, 2020)
The free radical is an unstable molecule because contains one or two unpaired electrons. The antioxidant substance is a simple way to decrease the illness caused by free radicals. Cawat hanoman (Bauhinia aculeata L.) was known to contain tannin components one of the benefits as an antioxidant. This research aims to determine the antioxidant activity of the B. aculeata stem tested by qualitatively used thin-layer chromatography (TLC) and quantitatively using the DPPH method. Bauhinia aculeata stem was extracted using a maceration extract method with 96% ethanol. Antioxidant activity test was done qualitatively by eluent of ethyl acetate : methanol : purified water (6 : 2 : 1) using TLC and quantitatively using the DPPH method. The result of antioxidant activity from 96% ethanol extract of B. aculeata stem qualitatively showed the presence of yellow spots on a purple background at TLC after syringed DPPH 0.5 mM and quantitative test that resulted in an IC50 of 21.862 μg/mL. These results indicate that 96% ethanol extract of B. aculeata has very strong antioxidant activity.